PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MENULIS ARTIKEL OPINI SISWA KELAS XII - Fitri Sopiatu Saadah; Diena San Fauziya; Dede Abdurrokhman (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The lack of use of learning media, especially in Indonesian language subjects, causes students to easily get bored in the learning process which results in low student learning outcomes. This study aims to describe the changes obtained from the use of project-based interactive learning media that are effective for use. So that the type of approach used is descriptive quantitative. Data collection in this study was carried out by conducting a pre-test and post-test, with data analysis techniques using N-Gain to measure the increase in process skills during learning. Based on the results of data analysis, the results of the criteria for the N-Gain score obtained from the pre-test and post-test Gain scores obtained on average 0.7 in the first interval G≥0.7 = High. So it can be concluded that there is a high increase in skills between the pre-test and post-test. This shows that the use of project-based interactive learning media is successful in maximizing students' ability to develop ideas and compose good and correct opinion articles. So it can be concluded that Project Based Learning-based interactive learning media is in good qualification and is suitable for use as a learning resource for class XII Indonesian subjects.